(untitled) (UKLO Proceedings, 2025)
The paper addresses the UN sustainable Development Goals (SDGs) through the lens of English language instruction, centred around English for law enforcement. It elaborates on the link between SDGs and law enforcement and English language instruction, offering ideas for presenting SDGs-related topics and vocabulary in the classroom. It focuses on classroom activities for presenting vocabulary on gender-based violence in English, in the context of SDG5 - Gender Equality. The suggested activities are aimed at raising learners’ awareness of the importance of the issue of gender equality through elaboration of this topic and acquisition of gender-based violence vocabulary. They will help them identify the semantic nuances between different concepts related to gender-based violence and will also enhance their professional skills necessary for their future profession, including the achievement of the SDGs linked to law enforcement.